THU0020 COMPARATIVE STUDY OF THE PHOSPHODIESTERASE TYPE 5 INHIBITOR SILDENAFIL AND THE PROSTACYCLIN ANALOGUE ILOPROST ON IP10 MODULATION IN SYSTEMIC SCLEROSIS. (June 2019) - Crescioli, Clara; Riccieri, Valeria; Stefanantoni, Katia; Corinaldesi, Clarissa; Vasile, Massimiliano; Marampon, Francesco; Valesini, Guido; Lenzi, Andrea; Luigi, Luigi DI; antinozzi, cristina
Abstract : Background: Systemic sclerosis (SSc) is an autoimmune disease ending in multiorgan fibrosis. Vascular damage, responsible for the vascular alteration and disruption, has been suggested to play a key role in disease maintenance and progression [1]. Recent data demonstrated that high serum levels of the interferon (IFN)-γ-induced protein 10 (IP-10) in SSc patients correlated with peripheral vascular injure and increased in association with nailfold capillaroscopic pattern worsening and digital ulcers presence [2, 3]. Between the vasoactive drugs used for SSc treatment, the prostacyclin analogue iloprost (I) and PDE-5 inhibitor sildenafil (S) seem to have high vasodilatatory and immunomodulatory actions [4-6]. Objectives: To investigate and compare the ability of S and I to modulate: IP-10 circulating levels in SSc patients under different treatments; IP-10 release by human endothelial (Hfaec) cells subjected to Th1-related inflammatory stimuli. Methods: Sera of 28 patients satisfying ACR/EULAR 2013 classification criteria for SSc were analyzed by ELISA. IFNγ+TNFα-induced activation of NFkB, STAT1, JNK, ERK1/2 and AKT in Hfaec after S or I was tested by Western blot. Results: The treatment with S significantly reduced IP-10 serum levels vs. treatment with (DMARDS) and corticosteroids (CCs) (184.1±65.10 vs. 880.9±339.0 pg/ml and vs. 426.5±101.7, respectively, P<0.01); while no significant difference has been found vs. I (184.1±65.10 vs. 282.7±46.6 pg/ml). In Hfaec, S and I differently counteracted the IFN-γ/TNF-α-induced phosphorylation of JNKs (respectively 61.6.0±20.1% and 9.5±13.1% of phosphorylation vs. I+T-induced taken as 100%), STAT1 (respectively 49.2±15.8% and 93.4±1.2% of phosphorylation vs. I+T-induced taken as 100%), NFkB (respectively 72.6±8.3% and 92.2±3.3% of phosphorylation vs. I+T-induced taken as 100%), ERK1/2 (respectively 31.6±7.9% and 27.3±4.4% of phosphorylation vs. I+T-induced taken as 100%), and AKT (respectively 85.7±5.6% and 3.8±7.4% of phosphorylation vs. I+T-induced taken as 100%). Conclusion: In vivo results show that S and I have more effect in targeting serum IP-10 in SSc patients than other therapeutic treatments. In vitro data show different inhibitory drug-induced effects onto paths underlying IP-10 production, depending on intracellular targets. S could be a potential pharmacological tool as effective as I to control IP-10 in blood or at endothelial cell level in SSc. References: [1] Varga J, et al., 2007. [2] Antonelli A, et al., 2008. [3] Crescioli C, et al., 2018. [4] Scorza R, et al., 2001. [5] Higuchi T, et al., 2015. [6] Hassoun PM, et al. 2015. Disclosure of Interests: clara crescioli: None declared, Valeria Riccieri: None declared, Katia Stefanantoni Consultant for: Only 1 scientific advice for Italfarmaco in 2016, clarissa corinaldesi: None declared, massimiliano vasile: None declared, francesco marampon: None declared, Guido Valesini: None declared, andrea lenzi: None declared, luigi di luigi: None declared, cristina antinozzi: None declared